An Excel-Based Stock Management System for a Leather Label Manufacturer - UÇUCU, EMİNE; ERASLAN, FATMA BEYZA; KAYMAKLI, ZEYNEB NUR; EMİR, OĞUZ; AKTİN, AYŞE TÜLİN (Springer Science and Business Media Deutschland GmbH, 2024)
This paper presents a proposal for an Excel-based digital inventory tracking system to address the operational challenges faced by a leather label manufacturer located in Istanbul, Turkey. The company is currently reliant on manual stock keeping and tracking methods for its leather labels and raw materials, resulting in significant functional difficulties due to the absence of a systematic and efficient inventory tracking system. The proposed system aims to enhance overall productivity and decision-making processes within the company. By implementing the new tracking system, the company can overcome the limitations of manual stock management, leading to improved efficiency and organization in inventory control. Furthermore, the installation of a barcode system is suggested to augment the tracking system’s capabilities, and the profitability of the proposed system is evaluated using three different financial analysis methods. This research contributes to the advancement of inventory management practices and provides valuable insights into the potential benefits of adopting digital solutions for stock control in the leather label industry. © The Author(s), under exclusive license to Springer Nature Switzerland AG 2024.
International Symposium for Production Research, ISPR 2023
Keywords: Economic Analysis; Excel VBA; Leather Label Manufacturing; Stock Management; Stock Tracking